Comparison of Full Endoscopic Lumbar Diskectomy Using the Transforaminal Approach versus Interlaminar Approach for L5–S1 Lumbar Disk Herniation Treatment: A Meta-Analysis - Zhu, Ming-Tao; Hu, Bao-Shan; Chen, Chien-Min; Liu, Hong-Qi; Lin, Guang-Xun (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Numerous studies have examined the clinical effectiveness of transforaminal full endoscopic lumbar diskectomy (T-FELD) and interlaminar full endoscopic lumbar diskectomy (I-FELD) for L5–S1 lumbar disk herniation (LDH), with mixed findings. The goal of this systematic review and meta-analysis was to evaluate the perioperative outcomes, clinical results, and complications of T-FELD and I-FELD to determine their efficacy and safety for treating L5–S1 LDH and to examine the features of complications in depth.Methods Several databases were searched for articles that matched all of the inclusion criteria. The visual analog scale (VAS) and Oswestry Disability Index (ODI) were used to assess the clinical results. Information on perioperative outcomes and complications was gathered and analyzed.Results Eight studies with 756 participants were included. There were no significant differences in postoperative bed time (p = 0.44) and hospitalization time (p = 0.49) between T-FELD and I-FELD. When compared with I-FELD, T-FELD was associated with substantially longer fluoroscopy time (p < 0.0001) and operating time (p < 0.0001). There were no significant differences in the preoperative and postoperative VAS and ODI scores between T-FELD and I-FELD. The rates for overall complications, postoperative dysesthesia, postoperative lower extremity pain, incomplete decompression, recurrence, and conversion to open surgery were comparable for T-FLED and I-FELD.Conclusion T-FELD and I-FELD had equal clinical results and safety for treatment of L5–S1 LDH. Fluoroscopy and operative times were shorter for I-FELD than for T-FELD.
Keywords: full endoscopic lumbar diskectomy; transforaminal; interlaminar; L5–S1; lumbar disk herniation